Child Protection of Perpetrators of Terrorism in Indonesia: How should we do? Should we punish them? - Akbar, Athayya (Indonesian Journal of Counter Terrorism and National Security, 2024)
In Indonesia, the issue of child protection within the context of perpetrators of terrorism presents a multifaceted challenge that necessitates a careful balance between justice and rehabilitation. This paper delves into the complexities surrounding this issue, acknowledging the rights and well-being of children while addressing the imperative for accountability and security. While children may be both victims and perpetrators of terrorism, the prevailing question is how to effectively respond to their involvement. This paper examines the existing legal frameworks in Indonesia, international standards, and the various challenges encountered in implementing appropriate strategies. It considers the identification and assessment of affected children, the efficacy of rehabilitation and reintegration programs, as well as the importance of psychological and social support. Moreover, it highlights the significance of community perceptions and the risk of stigmatization, as well as the need for long-term monitoring to prevent recidivism. Ultimately, this paper advocates for a comprehensive approach that combines punitive measures with rehabilitation efforts, emphasizing the importance of multi-agency collaboration, educational initiatives, psychosocial support, and legal safeguards. Through case studies and lessons learned, it aims to inform policymakers and practitioners in Indonesia on effective strategies for ensuring the protection and well-being of children involved in terrorism while upholding principles of justice and accountability.